Pelatihan SIAPIK Berbasis Android untuk Mengoptimalisasi Pengelolaan Keuangan UMKM Syariah di Kabupaten Bangka - Marheni, Marheni; Ulyah, Himmatul; Rizki, Rizki (Jurnal Pengabdian UNDIKMA, 2022)
This community service aims to provide bookkeeping and financial reporting training using the Android-based SIAPIK application program for sharia UMKM players in the Bangka district. The methods of implementing this service activity were offline training and mentoring methods. This service targeted 26 sharia MSME actors in the Bangka district. The evaluation instrument for this activity used Quizzes and test questions. The results of this service showed that the SIAPIK training had increased the understanding of UMKM actors about the importance of financial management for micro, small, and medium enterprises, as well as the practice of preparing financial reports using the SIAPIK application. The SIAPIK application is expected to make it easier to make financial reports useful for business decisions and applying for capital loans from creditors.